Mud and Mudstones Introduction and Overview - Potter, Paul E.; Maynard, J. Barry; Depetris, Pedro J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
Mud and mudstone, the most abundant of all sediments and sedimentary rocks, are relevant to many different human activities and disciplines and thus have a widely scattered literature. Our book provides the first elementary overview of mud and mudstone written for a broad spectrum of professionals, teachers and students in geology, petroleum geology and engineering, urban planning and development, paleontology and paleoecology, and architecture and archaeology. Mud and mudstone provide the foundations to master all their aspects and prepares you to dig deeply into the many fascinating questions of their origin, relationships to earth history and practical uses. Key topics include the production of mud, its transport, the important role of bottom oxygen, sites of deposition, burial, provenance, mudstones in basins and an overview of practical uses followed by an appendix and extended glossary.
Overview -- Production of Mud and Silt -- Transport and Deposition -- Role of Oxygen -- Muddy Depositional Systems -- Burial -- Provenance of Mudstones -- Muddy Basins -- Practicalities.
Keywords: Geography; Geology; Paleontology; Sedimentology; Geomorphology; Geography; Geomorphology; Geology; Sedimentology; Paleontology; Electronic books